Influence of crank rate in hand cycling - Verellen, J.; Theisen, D.; Vanlandewijck, Y. (Medicine & Science in Sports & Exercise, 2004)
Purpose: The purpose of this study was to determine gross mechanical efficiency (ME) at different power output (PO) levels of synchronous hand cycling and to evaluate the influence of increasing PO by changing crank rate or resistance in wheelchair users with experience in hand cycling. Methods: Nine male participants with spinal cord injury randomly performed three maximal incremental hand cycling tests using a computer controlled cycle ergometer. Each test started at a PO level of 50 W with increments of 10 W. In the velocity protocol, PO was increased via crank rate while resistance was constant (VEL). In the resistance protocol PO was increased via resistance while crank rate was constant (RES). In the freely chosen frequency protocol, the participants could freely select their crank rate while resistance was automatically adjusted to obtain the desired PO (FCF). Results: Peak physiological responses were similar in all three tests, whereas PO max was lower in VEL compared with RES and FCF. Similar values for gross ME were found in both RES and FCF protocols, although systematically higher and increasing crank rates were adopted throughout FCF. Nevertheless, differences in gross ME at comparable relative (RES > VEL at 60 and 80% of PO range: 14.09 and 14.40% vs 13.02 and 13.11%, respectively) and absolute (RES, FCF > VEL at 90 W: 14.47, 14.47, and 13.43%, respectively) PO levels were demonstrated. Conclusion: These results suggest that during synchronous hand cycling the freely chosen crank rate is not necessarily the most economical, that high crank rates result in a lower ME at a given PO and that freely chosen crank rates increase with increasing PO levels.